Effects of Entecavir on Hepatitis B Virus Covalently Closed Circular DNA in Hepatitis B e Antigen-Positive Patients with Hepatitis B - Shi, Ming; Sun, Wan-Li; Hua, Yan-Yan; Han, Bo; Shi, Long (PLOS ONE, 2015)
The aim of this study was to assess the effect of 48-week entecavir therapy on serum and intrahepatic hepatitis B virus, covalently closed circular DNA (HBV cccDNA) levels in hepatitis B e antigen (HBeAg)-positive patients. A total of 120 patients with HBeAg-positive chronic hepatitis were treated with entecavir for 48 weeks. Serum HBV markers, total HBV DNA, and HBV cccDNA levels were measured at baseline and week 48. Biopsies from 20 patients were available for both intrahepatic total HBV DNA and cccDNA testing at these timepoints. HBV cccDNA levels were decreased from a median level of 5.1×106 copies/mL at baseline to a median level of 2.4×103 copies/mL at week 48. Reduction magnitudes of HBV cccDNA in patients with normalized alanine aminotransferase levels and those undergoing HBeAg seroconversion were significantly greater than those in alanine aminotransferase-abnormal and HBeAg positive patients. Intrahepatic HBV cccDNA was decreased significantly after 48 weeks of treatment, but could not be eradicated. In conclusion, treatment of HBeAg-positive hepatitis B patients with entecavir for 48 weeks decreased serum and intrahepatic HBV cccDNA significantly, and the magnitude of HBV cccDNA reduction was related to total HBV DNA decrease, alanine aminotransferase normalization, and HBeAg seroconversion.